Plans, Progression and Post-Compulsory Education: Measuring the Success of a School–University Widening Participation Programme in Ireland - Eilís Ní Chorcora; Joanne Banks; Aibhín Bray (Social Sciences)
It is widely recognised that addressing inequality in tertiary education is a complex and multifaceted issue. Studies involving students from lower socio-economic backgrounds consistently show that educational disparities exist at the post-secondary education level, with these students’ encountering obstacles in both accessing and completing tertiary education compared to their wealthier counterparts. Understanding how widening participation interventions may influence young people’s post-compulsory education is an important part of addressing the participation gap. This paper investigates longitudinal data from 227 students in Dublin, Ireland, who were attending post-primary schools located in areas that have low progression to tertiary education. The paper examines the extent to which students’ post-secondary plans, formulated in their final year of secondary school, are realised six months after graduation. The paper continues to examine the influence of external interventions provided by an Irish university’s widening participation (WP) programme on secondary school students’ progression to post-compulsory education. Taking into account contextual factors (e.g., gender, ethnicity, school type, parental education, parental support), this paper examines how WP programmes in secondary school impact post-school progression. Programme engagement (guidance outreach activities) was associated with 4.91-greater odds of post-secondary education once other contextual factors had been controlled for. Participating in mentoring programmes did not have a significant influence on post-secondary progression. Findings in relation to these are discussed, and recommendations for how practitioners and policy makers can approach widening participation outreach programmes with secondary school students are highlighted.